2018
DOI: 10.1007/s10072-018-3489-9
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific methylation contributed by CpG-SNP is associated with regulation of ALOX5AP gene expression in ischemic stroke

Abstract: Previous studies have shown that CpG-SNPs might have influence on gene function via allele-specific DNA methylation (ASM). However, association study between DNA methylation and the promoter CpG-SNPs in ALOX5AP gene with IS has not been reported. The present study aims to explore the relationship among CpG-SNPs, methylation levels, and messenger RNA (mRNA) expression levels of ALOX5AP gene. Firstly, we made a two-stage association study to identify a potential associated CpG-SNP (rs4073259) by SNaPshot genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the case of CVDs, the PEAR1 gene and ALOX5AP gene have been associated with the disease [19, 116]. PEAR1, as discussed earlier, plays a role in cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of CVDs, the PEAR1 gene and ALOX5AP gene have been associated with the disease [19, 116]. PEAR1, as discussed earlier, plays a role in cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%
“…The ALOX5AP gene codes for 5-lipoxygenase-activating protein and is a risk factor for ischemic stroke. Two CpG SNPs, namely, rs12041331 in the PEAR1 gene and rs4073259 in the ALOX5AP gene, affect the expression of genes through allele-specific methylation and contribute to platelet reactivity and ischemic stroke, respectively [19, 116].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the methylation levels of CpG8 were significantly different from other sites due to the generation of a CpG site. In a previous study conducted by our group, IS-associated CpG-SNP rs4073259 correlated with differential DNA methylation, presenting the phenomenon of allele-specific methylation which may elucidate the phenotypic effects of certain genetic variants ( 25 ).…”
Section: Discussionmentioning
confidence: 94%
“…After duplicates were removed, 176 studies remained. On examination of the full text, 30 papers were eligible for inclusion in the review 1140. Study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, four Asian studies providing summaries of data on the ALOX5AP rs4073259 polymorphism did not find any association with IS risk (OR=1.20 for A allele vs G allele; 95% CI: 1.00–1.45; P =0.056) (Table 2). 21,30,40…”
Section: Resultsmentioning
confidence: 99%